PEMBUATAN MINYAK KELAPA MURNI (Virgin Coconut Oil, VCO) MELALUI KOMBINASI TEKNIK FERMENTASI DAN ENZIMATIS MENGGUNAKAN GETAH PEPAYA - Ramlan Silaban; Vivi Hutapea; Riza Manullang; Irving Josafat Alexander (Jurnal Pendidikan Kimia (JPKim), 2014)
Abstract. This study aims to determine the yield of Virgin Coconut Oil (VCO) is made through a combination of fermentation and enzymatic techniques using papaya latex. Previous papaya sap is processed into crude papain enzyme and fermentation using yeast tempeh (Rhizopus oligosporus). Concentration of 100 ml coconut milk is added 0.5 grams of tempeh and coarse with variation of the enzyme papain 0.0 grams; 0.2 grams; 0.4 grams; 0.6 grams; 0.8 grams and with a pH of 3.4 and 5 variations of this mixture was incubated for 24 hours at room temperature. Of 100 mL of milk obtained optimum yield Virgin Coconut Oil (VCO) of 27.8 mL of the enzyme at a concentration of as much as 0.6 grams of crude papain at pH 5. addition of the enzyme papain is able to increase the yield of coarse Virgin Coconut Oil (VCO), but at a certain concentration will be able to lower the yield. The lower the pH, the lower the yield of Virgin Coconut Oil (VCO) is obtained. Analysis of the quality of Virgin Coconut Oil (VCO) in terms of free fatty acid 0.1720%, 0.18% and a water content of 9.45 mg iodine / g. The Virgin Coconut Oil (VCO) obtained had been met requirement set by SNI standard’s. Kata kunci: Virgin Coconut Oil (VCO), Getah Pepaya, Ragi Tempe